2021
DOI: 10.3390/jpm11111216
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Spatiotemporal Dynamics of the Brain at Rest and Self-Reported Spontaneous Thoughts: An EEG Microstate Approach

Abstract: Rationale: The resting-state paradigm is frequently applied in electroencephalography (EEG) research; however, it is associated with the inability to control participants’ thoughts. To quantify subjects’ subjective experiences at rest, the Amsterdam Resting-State Questionnaire (ARSQ) was introduced covering ten dimensions of mind wandering. We aimed to estimate associations between subjective experiences and resting-state microstates of EEG. Methods: 5 min resting-state EEG data of 197 subjects was used to eva… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 63 publications
2
13
0
Order By: Relevance
“…This should prove helpful, especially for specific participants with disorders who might have a reduced msD, for example, the system with a regular parameter should be less responsive to them than to healthy participants. Finally, the definition of a state as a canonical EEGms and the number of microstates are controversial (Michel and Koenig, 2018;Tarailis et al, 2021). Further studies should address this issue, since the current study used traditional definitions.…”
Section: Discussionmentioning
confidence: 90%
“…This should prove helpful, especially for specific participants with disorders who might have a reduced msD, for example, the system with a regular parameter should be less responsive to them than to healthy participants. Finally, the definition of a state as a canonical EEGms and the number of microstates are controversial (Michel and Koenig, 2018;Tarailis et al, 2021). Further studies should address this issue, since the current study used traditional definitions.…”
Section: Discussionmentioning
confidence: 90%
“… Pipinis et al (2017) found a negative association between microstate C and experienced somatic awareness (SA) of the subsequent Amsterdam Resting-State Questionnaire (ARSQ). SA was evaluated by questions related to bodily self-consciousness (e.g., “I was conscious of my body”; “I thought about my heartbeat”; “I thought about my breathing.” In a follow-up study, Tarailis et al (2021) showed that microstate F was associated with SA, microstates C, E, and G were related to the comfort domain and microstates B and C related to the self-domain. Zanesco et al (2021b) directly examined the association between episodes of mind wandering and microstates in a cognitive task with embedding experience sampling probes to capture moments of on-task vs. off-task focus.…”
Section: Eeg Microstates In Self-related Mind-wanderingmentioning
confidence: 97%
“…The ARSQ appeared to be a useful tool to relate biological signals collected over the resting-state session with participants’ subjective experiences and emotions. Several studies using different brain-imaging modalities and applying different analysis methods have reported associations with the ARSQ domains (DoM [ 24 , 26 ], ToM [ 20 ], Self [ 25 , 26 ], Planning [ 18 , 22 ], Sleepiness [ 16 , 24 ], Comfort [ 18 , 24 , 25 ], Somatic Awareness [ 18 , 21 , 25 , 26 ], Visual Thought [ 24 ], and Verbal Thought [ 26 ]). However, none of the studies has implemented an f-PCA approach for EEG quantification.…”
Section: Discussionmentioning
confidence: 99%
“…The Comfort domain was characterized by questions such as “I felt comfortable”, “I felt happy”, and “I felt relaxed”. Previously, this domain has been associated with the temporal characteristics of broadband EEG microstates C, E, G [ 25 ], and D [ 18 ]. EEG microstates are mainly driven by alpha activity [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation